Anagrelide, a novel agent in the treatment of essential thrombocythemia - Wieczorek, Jolanta; Nowicka, Urszula (Contemporary Oncology/Współczesna Onkologia, 2001)
Essential thrombocythemia (ET), like polycythemia vera, chronic myelogenous leukemia, myelofibrosis, belongs to the chronic myeloproliferative disorders (MPD). ET is less likely than other MPDs to convert spontaneusly to acute leukemia. Like the other MPDs, however, bleeding and thrombosis are major causes of morbidity and mortality. Platelet-lowering agents currently used in ET include hydroxyurea, pipobroman, INFα, busulfan, radiophosphorus. Anagrelide is a neworal imidazoquinazoline derivative approved for use in ET and other MPDs as a platelet-lowering agent. The mechanism of action may involve the drug's interference with megacaryocyte maturation. More than 90% of patients with ET respond to anagrelide therapy regardless of the presence r absence of previous therapy. The responses are durable with median maintenence dose of aproximately 2 to 2.5 mg/day. Side efects are related mostly to the drug's vasodilating and positive inotropic efects. The place of anagrelide therapy in the current management of patients with ET is discussed.